Understanding Forest Fire Management in Indonesia from a Global Perspective - Indra Agus Riyanto; Ahmad Cahyadi; Faricha Kurniadhini; Hafidz Bachtiar; Dwiki Apriyana; Brian Kannardi Aji Caraka (Universitas Gadjah Mada, 2020)
Forest fires are one of the global issues that attract worldwide attention. Russia, Brazil, Canada, the United States, and Indonesia are among the countries with the largest forest cover and long records of massive forest fires. Forest fire management is, therefore, critical to decreasing the severity level of these fires. Current conditions indicate that, compared with the four other countries, Indonesia has significantly reduced forest fires within the past five years. Consequently, adopting a global perspective to study the characteristics of forest fire disaster management has become necessary. For each management parameter, this research employed a literature review and descriptive analysis. The results showed that Indonesia had an advantage in the field of legal regulation. Indonesia tends to change its regulations within a short span of time, resulting in the number of forest fire incidents decreasing significantly compared with Russia, Brazil, Canada, and the United States. However, the country still has several weaknesses, namely in emergency responses, forest fire monitoring technology, and inter-institutional integration in forest fire disaster management.